PARAMETERS OF ELECTRONIC STRUCTURE AND FORBIDDEN ENERGY IN INAS ZINC BLENDE CRYSTALLINE ALLOY - Cabrera Arista, César (2023)
The use of semiconductor materials such as indium arsenide alloy is increasing in new applications, due to their electronic properties and great potential as an optoelectronic material. In the present study, the parameters of electronic structure and the energy-forbidden gap of indium arsenide with zinc blende crystal structure were calculated. The method of the linear muffins tin orbitals LMTO with an LDA potential using the exchange and correlation approximation of a homogeneous spin-polarized electron gas was used to solve the Schrödinger equation of the crystal lattice of the InAs. The energy bands, state density, and total energy were calculated for six different cases of a small fraction of the valence electron charge on the empty diagonal spheres in the lattice. The electronic structure had a forbidden energy gap of 0.408 eV associated with the minimum total energy of −18.12 Ry close to the experimental results.